2010
DOI: 10.1128/jb.01328-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C-Terminal Cytoplasmic Domain of FlhA in Bacterial Flagellar Type III Protein Export

Abstract: For construction of the bacterial flagellum, many of the flagellar proteins are exported into the central channel of the flagellar structure by the flagellar type III protein export apparatus. FlhA and FlhB, which are integral membrane proteins of the export apparatus, form a docking platform for the soluble components of the export apparatus, FliH, FliI, and FliJ. The C-terminal cytoplasmic domain of FlhA (FlhA C ) is required for protein export, but it is not clear how it works. Here, we analyzed a temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 30 publications
4
74
0
Order By: Relevance
“…These observations suggest that FliI requires FliH to support the function of the FlhA mutants. and FlhB C provide binding sites for FliH, FliI, FliJ, flagellar chaperones, and export substrates (1,25,29,32,34,36,50). Because the reduced secretion activity of the fliH null mutant is significantly improved by the overexpression of FliI or extragenic suppressor mutations in FlhA or FlhB, FliH is thought to be required for the productive association of FliI with the FlhA-FlhB complex (25).…”
Section: Isolation Of Mutations That Cause Loss Of An Inhibitory Funcmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that FliI requires FliH to support the function of the FlhA mutants. and FlhB C provide binding sites for FliH, FliI, FliJ, flagellar chaperones, and export substrates (1,25,29,32,34,36,50). Because the reduced secretion activity of the fliH null mutant is significantly improved by the overexpression of FliI or extragenic suppressor mutations in FlhA or FlhB, FliH is thought to be required for the productive association of FliI with the FlhA-FlhB complex (25).…”
Section: Isolation Of Mutations That Cause Loss Of An Inhibitory Funcmentioning
confidence: 99%
“…The export apparatus consists of a membrane-embedded export gate made of six membrane proteins, FlhA, FlhB, FliO, FliP, FliQ, and FliR, and a water-soluble ATPase complex consisting of FliH, FliI, and FliJ (22,28). The C-terminal cytoplasmic domains of FlhA (FlhA C ) and FlhB (FlhB C ) provide binding sites for the ATPase complex, flagellar substrate-specific chaperone, and export substrates (1,25,29,32,34,36,50). FlhB C acts as the export specificity switch to mediate the ordered export of the axial flagellar components during flagellar assembly (19).…”
mentioning
confidence: 99%
“…FlhA C consists of a compactly folded core domain (FlhA C 38K) formed by four subdomains-D1, D2, D3, and D4 -and a flexible linker region (FlhA L ), which connects FlhA C 38K to the N-terminal integral membrane domain (FlhA TM ) with eight predicted transmembrane helices (15,34,42). It has been shown that FliJ binds to FlhA L (16,27).…”
Section: Inhibitory Effect Of Gst-flij On Flagellar Protein Exportmentioning
confidence: 99%
“…The C-terminal cytoplasmic domains of FlhA (FlhA C ) and FlhB (FlhB C ) provide the docking sites for FliH, FliI, FliJ, flagellar chaperones, and export substrates (13)(14)(15)(16)(17). FliI is a Walker-type ATPase (18) and forms a stable FliH 2 -FliI complex with FliH (19).…”
mentioning
confidence: 99%
“…FliJ also was proposed to recycle substrate-free flagellar chaperones at the export gate (24). FliI, FliH, and FliJ bind to FlhA and FlhB proteins at the export gate (11,25,26).…”
mentioning
confidence: 99%